Oral Adenosine-5′-triphosphate (ATP) Administration Increases Postexercise ATP Levels, Muscle Excitability, and Athletic Performance Following a Repeated Sprint Bout. (3rd April 2017) - Purpura, Martin; Rathmacher, John A.; Sharp, Matthew H.; Lowery, Ryan P.; Shields, Kevin A.; Partl, Jeremy M.; Wilson, Jacob M.; Jäger, Ralf
Abstract: Objective : Oral adenosine-5′-triphosphate (ATP) administration has failed to increase plasma ATP levels; however, chronic supplementation with ATP has shown to increase power, strength, lean body mass, and blood flow in trained athletes. The purpose of this study was to investigate the effects of ATP supplementation on postexercise ATP levels and on muscle activation and excitability and power following a repeated sprint bout. Methods : In a double-blind, placebo-controlled, randomized design, 42 healthy male individuals were given either 400 mg of ATP as disodium salt or placebo for 2 weeks prior to an exercise bout. During the exercise bout, muscle activation and excitability (ME, ratio of power output to muscle activation) and Wingate test peak power were measured during all sprints. ATP and metabolites were measured at baseline, after supplementation, and immediately following exercise. Results : Oral ATP supplementation prevented a drop in ATP, adenosine-5′-diphosphate (ADP), and adenosine-5′-monophosphate (AMP) levels postexercise ( p < 0.05). No group by time interaction was observed for muscle activation. Following the supplementation period, muscle excitability significantly decreased in later bouts 8, 9, and 10 in the placebo group (−30.5, −28.3, and −27.9%, respectively; p < 0.02), whereas ATP supplementation prevented the decline in later bouts. ATP significantly increased Wingate peak power in later bouts compared to baseline (bout 8: +18.3%, bout 10: +16.3%). Conclusions : Oral ATP administration prevents exercise-induced declines in ATP and its metabolite and enhances peak power and muscular excitability, which may be beneficial for sports requiring repeated high-intensity sprinting bouts.